Hadits Tentang Pendidikan Keluarga - Siti Ardianti; Khairunnisa Gajah, Rizkiyah; Bayu Pratama, Krisna; Nasution, Nafia Safitri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Education is one of the most important things in a group. After birth, the baby's immediate environment is considered family. As an individual, you have the responsibility and ability to discern, and share knowledge that is fundamental to secular and sacred life. With these two knowledge, a person is able to succeed globally and fail in the afterlife. And the first time a child learns about global matters is where his parents come from. according to them, a child shares every aspect of his privacy. In this case, the father is not the only father, on the other hand, the father is also the party who cares for, protects and gives birth to children. For this reason, fathers can provide their children with a good and trustworthy education from birth, as a result of which the child's growth and development stimulates the development of life lessons that are beneficial for the mother, the people and other people in the surrounding environment.